Conditions of small towns’ historic environment formation and development - Velichko, Svetlana (Lira-K, 2016)
To create competent reconstruction projects in historic urban environment it is necessary to carry out pre-project analysis of formation and development conditions and factors of architectural urban environment of a small town’s historical center. Historic environment is viewed as an object of the research, the components of which have been created during a certain historical period of the town’s development. The historical period must be characterized by certain evolutionary development patterns. The aim of the historic urban environment redesign is to preserve the town’s originality in the process of historical center reconstruction. Taking into consideration the results of preconception studies, it is essential to carry out further research of historical center’s values. The article deals with the analysis of the main formation and development conditions of small towns’ historic environment.
Условия формирования и развития исторической среды малых городов
Keywords: continuity principle; historic environment originality; time-layers; forming factors; the evolutionary process; принцип преемственности; своеобразие исторической среды; временные наслоения; формирующие факторы; эволюционный процесс